Needs Assessment for Computer-Based Medical Decision Support Systems - Berner, E. S. (1988)
Computer-based medical decision support systems should be developed with a clear understanding of physicians' needs for such support, yet these needs are rarely assessed. In order to identify the type of information that is needed for decision support, this study examined the correspondence between the knowledge base of QMR, a diagnostic support system for Internal Medicine, and the requests from internists and family physicians to MIST, a telephone consultation service based at an academic medical center. Results showed that the QMR knowledge base contained the majority of consultation requests made by the callers and that a small number of conditions account for most of the requests.